Industry Modernization Based on the Principles of Smart Specialization. Part I. Using the Key Enabling Technologies as a Priority of the EU Industrial Policy - Salikhova, O. B. (Statistics of Ukraine, 2019)
The concept of smart specialization is investigated with emphasis on key components of its successful implementation. Its relation with the concepts of technology, innovation and industrialization is shown through their common goal: to increase the productivity and ensure the sustainable economic growth. An analytical review of the official European documents elaborating the mechanisms for industry modernization and the principles for the new strategy of building the smart, innovative and sustainable industry, to promote competitiveness, creation of hybrid jobs and economic growth, is made. The critical role of key enabling technologies, especially advanced industrial technologies, in modernizing industry and implementing the smart specialization strategy is highlighted. The European Commission initiatives are analyzed, aimed at implementing the programs on competitiveness enhancement in the small and medium business sector, their implementation measures, including ones on constructing statistical tools for monitoring and analysis of generation and use of advanced technologies in the context of technological innovations in the private sector. The methodological approaches to building a new set of statistical indicators are supposed to ensure approvals of political decisions on enhancing competitiveness in the EU industry through launching three specific and related actions: (i) support to the development of cross-regional investment projects in the framework of S3P-Industrial Modernization; (ii) support to the development of European strategic cluster partnerships for cooperating in thematic fields and enhancing the industry’s role; (iii)) support to companies in the manufacturing industry in using advanced industrial technologies, in order to enhance their innovation capacities. It is noted that the program “Government Support to Technological Innovations for Industry Development” has not been launched in Ukraine, in spite of 300,000 UAH appropriated in the Budget – 2018 and the procedure for use of budget funds, created and coordinated with the central executive power bodies, by which the funds had to be allocated in implementing industrial innovation technologies in the private sector, for two purposes: (i) co-funding of project implementation; (ii) partial compensation for interest rates on loans received by manufactures for project implementation. The need to form the Strategy for Smart, Innovative and Sustainable Industry in Ukraine with consideration to directives and best practices of EU and the Ukrainian realities is emphasized.